The Relationship between Particulate Matter (PM10) and Meteorological Parameters in Ipoh, Perak (2020 - 2021) - Hashim, Mohd Hashiq; Ibrahim , Mohd Hairy (GEOGRAFI, 2023)
Air pollution is often associated with the level of suspended particles, especially PM₁₀ and is classified as one of the air pollutants. High levels of PM10 concentration will have a negative impact on the environment and human health. The objective of this study is to determine the level of PM10 concentration and the relationship of meteorological parameters which is, temperature, relative humidity and wind speed on particulate matter (PM10) in Ipoh, Perak. PM10 and meteorological parameters data collection were recorded directly at 10 sampling stations located around Ipoh. All data were taken for one week during the Southwest Monsoon (SWM), Northeast Monsoon (NEM) and inter-monsoon seasons. A non-parametric test (Spearman rank correlation) was used because the data were non-normal. The analysis showed that S6 had the highest average PM10 concentration within a week, with a value of 175.78 μg/m3. Temperature showed no correlation on PM10 concentration during SWM (ρ = 0.096), while NEM (ρ = 0.480) and inter-monsoon (ρ = 0.280) showed a positive correlation. The results also showed that PM10 and relative humidity had no relationship during SWM (ρ = 0.024), while NEM and inter-monsoon showed a negative correlation. Wind speed negatively correlated in all seasons (ρ = - 0448 to -0.126). Overall, the level of PM10 concentration level is influenced by an area's meteorological parameters.